Design, synthesis, and anti-inflammatory activity of 2H-1,4-benzoxazin-3(4H)-one derivatives modified with 1,2,3-triazole in LPS-induced BV-2 cells - Hou, Xixi; Mao, Longfei; Zhang, Huibin; Wang, Lan; He, Baoyu; Guo, Jingjing; Wang, Jianji (Frontiers in Pharmacology, 2025)
Given the potent anti-inflammatory properties of the 1,2,3-triazole structure and the wide use of 2H-1,4-benzoxazin-3(4H)-one in developing treatments for neurodegenerative diseases, a series of 2H-1,4-benzoxazin-3(4H)-one derivatives were synthesized by introducing a 1,2,3-triazole moiety. Screening for anti-inflammatory activity in microglial cells revealed that compounds e2, e16, and e20 exhibited the most promising effects without significant cytotoxicity. These compounds effectively reduced LPS-induced NO production and significantly decreased the transcription levels of pro-inflammatory cytokines IL-1β, IL-6, and TNF-α. Furthermore, they downregulated the transcription and protein levels of the inflammation-related enzymes iNOS and COX-2 in response to LPS stimulation. To further investigate the anti-inflammatory mechanisms of these derivatives in microglia, the intracellular ROS levels and the activation of the Nrf2-HO-1 signaling pathway were analyzed. The results indicated that the 2H-1,4-benzoxazin-3(4H)-one derivatives significantly activated the Nrf2-HO-1 pathway, reduced LPS-induced ROS production, and alleviated microglial inflammation. Molecular docking studies suggested that compounds e2, e16, and e20 could interact with Nrf2-related binding sites, preventing its degradation by Keap1. Additionally, acute toxicity tests in mice demonstrated that compound e16 exhibited favorable safety.